PROPOSED FORECASTING METHOD AND INVENTORY CONTROL METHOD FOR RINGER LACTAT 500 ML MJB AT ROYAL PRIMA HOSPITAL MEDAN (The Indonesian Journal of Business Administration, 2019)
Royal Prima Medan Hospital is a type B private hospital in Medan that has been accredited. Royal Prima Hospital must always provide the needs of its patients. In addition, one of the things that must be considered by the Hospital to maintain this accreditation is that it must always provide the medicine stock needed by the patient. In 2018, the Royal Prima Medan Hospital suffered a loss of opportunity costs of Rp 117,125,215 of one type of medicine, namely Ringer Lactat 500 ML MJB caused by out of stock.This research aims to assist the Royal Prima Medan Hospital, specifically to reduce the loss of opportunity costs caused by depleted medicine stocks. From 10 types of medicines that caused the biggest loss of opportunity costs at the Royal Prima Hospital in Medan, this research focused on the Ringer Lactat 500 ML MJB medicine which had the largest contribution, around Rp. 117,125,215. The method used in this study is the time series forecasting method and inventory control method. In addition, the author also developed an inventory ordering process to reduce the long lead time for ordering medicines. So the process of ordering medicines can done more effectively.After calculating the time series forecasting method and inventory control method, the author found the best method for the Royal Prima Medan Hospital. This method uses the estimated Holt Winter method with alpha 0.6 and gamma 0.6 and the fixed order quantity inventory control method. By applying these two methods, Royal Prima Medan Hospital can reduce the loss of opportunity costs around 49% or IDR 57,626,111 and reduce the total inventory cost around 45% or IDR 114,408,778. This helps the Royal Prima Medan Hospital to be more efficient and effective in carrying out its business.Keywords: Forecasting, Inventory Control, Hospital, Pharmacy